Role of Pr Substituted Eu-123 High Tc Cuprate Superconductors - Huse, V.R.; Mote, V.D.; Shah, S.S.; Dole, B.N. (Asian Journal of Chemistry, 2011)
The Pr substituted Eu1-xPrxBa2Cu3O7-δ high purity samples with compositions x = 0.0, 0.1, 0.2, 0.3, 0.4 and 0.5 were synthesized by ceramic route. The structural studies of all the samples were carried out by X-ray diffraction technique. The XRD studies of the samples show EuPr- 123 system have an orthorhombic pervoskite structure. The lattice parameters, volume of unit cell, oxygen deficiency, orthorhombicity, X-ray density and bulk density were evaluated using Rietveld refinement method. The lattice parameters, volume of unit cell and oxygen deficiency go on increasing while orthorhombicity, X-ray density and bulk density decrease as doping percentage of Pr increases. It may be due to the higher ionic radius or mixed valency or +3 or +4 valency state of praseodymium.